Speech Recognition and Speech Synthesis Repository System / Ng Koon Lee - Ng, Koon Lee (2002)
One of the advance computer technologies today perhaps is the system that able to communicate with the user via voice. From speak, user need not use hand frequently to control the system but with voice, all possible instruction can handle by the system do for user. This project main purpose is to build a system that able to show this technology especially in database. This project named Speech Recognition and Synthesis Repository System (SRn'SSRS). With this application, user can retrieve data from the database after setup. It works just like a search engine like Yahoo! but the information will be limited to faculty student information. This application will be support Malay language and also pointing device for user to interact with the computer. Development tool are from Microsoft Speech SDK5.x together with Microsoft Platform SOK and Microsoft Visual Studio. The programming language for development including Visual C++, COM, XML and HTML. For this system's function, it can let user to control 6 type of function which include: student registration information, student name list based on major, subject and year, list of subject in different semester and also student result. After the development a lot of test cases and testing method have been done. The strength and limitation of system conclude during using the system. Problem and solution was list out during testing. Future enhancement also was including in the project in order to enhance the system performance.